Kondisi Fisik Pemain Sekolah Sepakbola (SSB) Kota Padang - M Ridwan (Universitas Negeri Padang, 2020)
This research aims to analyze the physical condition of Padang Soccer School players. This is a descriptive research with 225 of population aged 14-15 years old and 100 participants as research sample. The data collection was conducted through physical condition tests, namely: arm muscle strength with push-up tests, abdominal muscle strength with sit-up tests, leg muscle explosive power with standing broad jump tests, agility with arrowhead agility test, speed with 30 meters running test, and endurance with 1,200 meters running test. The data obtained through the research instrument test were analyzed by using the percentage formula. The results of this research indicate that: 1) Arm muscle strength with an average of 39.0% are in the moderate category, 2) Abdominal muscle strength with an average of 42.00% are in the deficient category, 3) Leg muscle explosive power with an average of 35.0% in the medium category, 4) Agility with an average of 59.0% are in the medium category, 5) Speed ​​with an average of 42.0% are in the medium category, 6) Endurance with an average of 53.0% are in the medium category. In conclusion, based on all of the tests of this research, it showed that the physical condition of Padang Soccer School players are in the medium category. Thus, the players are expected to have more motivation to do physical practice as needed.